2020
DOI: 10.5539/ijel.v10n2p107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped Classroom Instruction on Developing Saudi EFL Learners’ Comprehension of Conversational Implicatures

Abstract: While pragmatic instruction has received considerable attention from researchers of interlanguage pragmatics over the last three decades, its effective implementation in the EFL classroom remains an unresolved question. The flipped classroom model is a recently developed teaching method that constitutes a role change for teachers and learners, inverting the front-of-class instruction paradigm in favor of active and collaborative classroom learning. To potentially take advantage of this promising trend, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Yet, technology integration enhances a student-centered approach to learning, and automated planning enables EFL students to improve and manage their regulation skills significantly within the online learning environment (Alsmari, 2020;Lee et al, 2020). Even with feasible technology, practical training remains one of the significant reasons which impedes Luddite teachers from integrating technology into teaching (Al-Saleh, 2018;Alnujaidi, 2021;Farooq & Soomro, 2018).…”
Section: Preparation Deficiencymentioning
confidence: 99%
“…Yet, technology integration enhances a student-centered approach to learning, and automated planning enables EFL students to improve and manage their regulation skills significantly within the online learning environment (Alsmari, 2020;Lee et al, 2020). Even with feasible technology, practical training remains one of the significant reasons which impedes Luddite teachers from integrating technology into teaching (Al-Saleh, 2018;Alnujaidi, 2021;Farooq & Soomro, 2018).…”
Section: Preparation Deficiencymentioning
confidence: 99%
“…Overall, there is little the researchers can do in terms of critically comparing the results of this study with previous studies since it explores a rather new territory. Studies on implicatures have mostly focused in the language learning classroom context, either in evaluating students' understanding and comprehension of implicatures (Alsmari, 2020;Derakhshan & Eslami, 2020) or investigating the effect of certain teaching models or learning technologies in the teaching of this pragmatics feature (Abdelhafez, 2016;Samaje & Ariyanmanesh, 2018). Many previous studies that investigated types of implicatures did not look at public service announcements, but works of literature such as The Pride and Prejudice novel (Wibawa, 2017), Princess Diaries novel (Budiaty, 2014), Beauty and the Beast movie (Tiara, 2018), Oedipus Rex play script (Megawati, 2019) and poems written by Audre Lorde (Igwedibia, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Their results were a continuation and proof of their previous study on the effectiveness of video-input for teaching pragmatics (Derakhshan, Mohsenzadeh, & Mohammadzadeh, 2014). Alsmari (2020) tries to see if flipped classroom instruction affected Saudi EFL learners' comprehension of conversational implicatures and found that effective out-of-class preparation and appropriate manipulation of in-class time did increase pragmatic competence.…”
Section: Implicaturementioning
confidence: 99%
“…As a result, empirical investigations have sought to securitize the effects of various contextual parameters that may activate the acquisition of L2 pragmatic competence, such as motivation, language proficiency, emotional intelligence, the educational setting, length of residence in a TL country, and metapragmatic discussions (Derakhshan & Eslami, 2015;Sánchez-Hernández & Alcón-Soler, 2019;Rafieyan et al, 2014;Roever, 2012;Takahashi, 2010a;Takahashi, 2010b). As pragmatics have increasingly proven to be amenable to intervention, ILP researchers and practitioners have begun examining the effectiveness of dichotomous teaching approaches and modes of instruction in comparison to others and exploring whether different teaching approaches yield different outcomes in various contextual settings, namely explicit vs. implicit, inductive vs. deductive, input vs. output-based instruction, and metapragmatic instruction, with a few studies focusing on the Arab World English Journal www.awej.org ISSN: 2229-9327 5 integration of modern technological tools into L2 pragmatics instruction (e.g., Alcón-Soler & Pitarch, 2010;Alsmari, 2020;Takahashi, 2010a).…”
Section: Introductionmentioning
confidence: 99%